Trust and Safe Spaces: Mental Health Consumers' and Carers' Relationships with Community Pharmacy Staff - Mey, A.; Knox, K.; Kelly, F.; Davey, A.; Fowler, J.; Hattingh, H. Laetitia; Fejzic, J.; McConnell, D.; Wheeler, A. (Wolters Kluwer Health/Adis, 2014)
Background: Trusting relationships between mental health consumers and health care providers are critical in the management and recovery process. Although community pharmacy staff are well placed to form relationships with mental health consumers and carers, little is known about the existence, nature or significance of consumer–staff relationships. Objectives: The aim of this study was to explore mental health consumers’ and carers’ perceptions of community pharmacy services, and describe the nature of their relationships with pharmacy staff. Methods: Focus groups and semi-structured interviews were conducted with a convenience sample of 74 mental health consumers or carers who self-selected into the study. Thematic analysis was undertaken to explore participants’ perspectives. Results: Positive experiences of pharmacy services were perceived to encourage consumers’ and carers’ trust in pharmacists and promote relationship development. This was enhanced when participants felt that elements of patient-centred care were part of the pharmacy services provided.Although some participants perceived community pharmacy to have a limited role in mental health, those who had established relationships highlighted the current role of pharmacists in their care, and appeared to welcome further extensions of pharmacists’ role in mental health. Conclusions: Trusting relationships between consumers and carers and community pharmacy staff were deemed to be important in mental health care and contributed to consumers’ and carers’ views of pharmacy as a safe health care space. Community pharmacy services that included core elements of patient-centred care appeared to facilitate relationship formation and associated benefits. Education and training is needed for community pharmacy staff to improve mental health knowledge and promote positive engagement with consumers and carers.